2020
DOI: 10.1039/c9dt03947c
|View full text |Cite
|
Sign up to set email alerts
|

M(H2O)(PO3C10H6OH)·(H2O)0.5 (M = Co, Mn, Zn, Cu): a new series of layered metallophosphonate compounds obtained from 6-hydroxy-2-naphthylphosphonic acid

Abstract: Layered metallophosphonates featuring phenol functions were obtained as single crystal and polycrystalline powders. Thermal stability, magnetic and luminescence properties are reported.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 75 publications
0
3
0
Order By: Relevance
“…The Cu(H 2 O)(PO 3 S 2 C 12 H 7 ) ( 5 ) compound exhibits three emission peaks at 3.97 eV (312 nm) (LI), 2.95 eV (420 nm) (LIII), and 2.39 eV (518 nm) (LIV), 1.97 eV (627 nm) (LV) which are characterized by a weak peak (LI), followed by two equally intense (LIII), (LIV), and (LV). Despite the Cu 2+ element being known as an emission quencher in studies, 63,64 the two most intense peaks can be attributed to the same transition observed in the ligand ( 3 ). The Co(H 2 O) 2 (PO 2 OH-S 2 C 12 H 7 ) 2 ( 6 ) compound presents several emission peaks at 3.61 eV (343 nm) (LI), 3.40 eV (364 nm) (LII), 2.98 eV (415 nm) (LIII), 2.43 eV (510 nm) (LIV) and, 2.0 eV (610 nm) (LV).…”
Section: Methodsmentioning
confidence: 94%
See 1 more Smart Citation
“…The Cu(H 2 O)(PO 3 S 2 C 12 H 7 ) ( 5 ) compound exhibits three emission peaks at 3.97 eV (312 nm) (LI), 2.95 eV (420 nm) (LIII), and 2.39 eV (518 nm) (LIV), 1.97 eV (627 nm) (LV) which are characterized by a weak peak (LI), followed by two equally intense (LIII), (LIV), and (LV). Despite the Cu 2+ element being known as an emission quencher in studies, 63,64 the two most intense peaks can be attributed to the same transition observed in the ligand ( 3 ). The Co(H 2 O) 2 (PO 2 OH-S 2 C 12 H 7 ) 2 ( 6 ) compound presents several emission peaks at 3.61 eV (343 nm) (LI), 3.40 eV (364 nm) (LII), 2.98 eV (415 nm) (LIII), 2.43 eV (510 nm) (LIV) and, 2.0 eV (610 nm) (LV).…”
Section: Methodsmentioning
confidence: 94%
“…Paper peaks at 3.97 eV (312 nm) (LI), 2.95 eV (420 nm) (LIII), and 2.39 eV (518 nm) (LIV), 1.97 eV (627 nm) (LV) which are characterized by a weak peak (LI), followed by two equally intense (LIII), (LIV), and (LV). Despite the Cu 2+ element being known as an emission quencher in studies, 63,64 ). The spectral similarity between the ligand and hybrid compounds suggests a shared origin for these two peaks.…”
Section: Dalton Transactionsmentioning
confidence: 99%
“…In recent decades, coordination polymers (CPs) or metal-organic frameworks (MOFs) have received extensive attention in research because they are tunable solids modulated by a limitless number of combinations of metal ions and organic ligands and have unique properties such as high porosity with a large surface area [4,5]. In addition, the proton conductivity of MOFs has received increasing attention from researchers [6,7] due to the presence of metal centers, organic linkers, and pore spaces. There have been several achievements in MOF materials with high proton conductivity by systematic design modifications, such as the introduction of NH 4 + , H 3 O + , and HSO 4 − into the pores of the framework [8].…”
Section: Introductionmentioning
confidence: 99%